CREATION OF A SOFTWARE SYSTEM FOR PRODUCT ACCOUNTING IN LOCAL ENTERPRISES (World Bulletin of Social Sciences, 2026)
This article considers the issues of automating product accounting processes in local enterprises. The possibilities of managing the warehouse, turnover, sales and customer service through a single system are analyzed. The importance and practical benefits of creating a simplified ERP system for small businesses are also highlighted. During the study, the methodology for developing a software system, its main functions and efficiency were studied. The results show that the use of automated systems increases productivity and reduces errors related to the human factor.
Keywords: product accounting; warehouse system; ERP; software system